A CoV2O4 precatalyst for the oxygen evolution reaction: highlighting the importance of postmortem electrocatalyst characterization. Issue 7 (5th January 2021) - Michaud, Samuel E.; Riehs, Michael T.; Feng, Wei-Jie; Lin, Chia-Cheng; McCrory, Charles C. L.
Abstract : Postmortem analysis of a CoV2 O4 catalyst for oxygen evolution reveals the active species is likely a vanadium-free amorphous cobalt oxide. Abstract : Vanadium-doped cobalt oxide materials have emerged as a promising class of catalysts for the oxygen evolution reaction. Previous studies suggest vanadium doping in crystalline Co spinel materials tunes the electronic structure and stabilizes surface intermediates. We report a CoV2 O4 material that shows good activity for the oxygen evolution reaction. However, postmortem characterization of the catalyst material shows dissolution of vanadium resulting in an amorphous CoO x material, suggesting that this vanadium-free material, and not CoV2 O4, is the active catalyst. This study highlights the importance of postmortem characterization prior to mechanistic and computational analysis for this class of materials.